2015
DOI: 10.1016/j.juro.2015.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Measures of Diabetes are Not Independent Predictors of Urinary Incontinence in Women

Abstract: Despite an increased prevalence of stress and urge urinary incontinence among women with diabetes, measures of diabetes mellitus type II are not independently associated with female incontinence. Rather, body mass index and several other characteristics are the dominant risk factors for stress or urge urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
14
0
3
Order By: Relevance
“…Individuals who experience LUTS are less likely than individuals with normal bladder function to achieve recommended levels of physical activity, 3 and women with LUTS have reported their symptoms as a barrier to physical activity and a contributor to weight gain. 4 As a potential barrier to physical activity, LUTS may increase the risk for obesity and related conditions, which is consistent with the strong association between urinary incontinence and both obesity 5-8 and diabetes 910 in women. Among the elderly, nocturia and urgency may increase risk for falls and fractures.…”
Section: Introductionsupporting
confidence: 61%
“…Individuals who experience LUTS are less likely than individuals with normal bladder function to achieve recommended levels of physical activity, 3 and women with LUTS have reported their symptoms as a barrier to physical activity and a contributor to weight gain. 4 As a potential barrier to physical activity, LUTS may increase the risk for obesity and related conditions, which is consistent with the strong association between urinary incontinence and both obesity 5-8 and diabetes 910 in women. Among the elderly, nocturia and urgency may increase risk for falls and fractures.…”
Section: Introductionsupporting
confidence: 61%
“…However, the impact of glycemic control on UI risk remains unclear. 16) Our study indicates that there is no association between UI and diabetes. This may be explained by a lack of data distinguishing the different types of UI.…”
Section: Discussionmentioning
confidence: 50%
“…Many studies have only used a self-reported history of diabetes in their analyses of associations between UI and diabetes. 16) Further studies are required to explain the relationships between different types of UI and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that biochemical measures, mainly hyperglycemia, are not independent predictors of the presence of urinary incontinence in DM patients 28 . Hsu, et al investigated the association of risk factors related to the presence of urinary incontinence in elderly DM subjects 29 .…”
Section: Discussionmentioning
confidence: 98%